PANTANGAN DAN LARANGAN MASYARAKAT DAYAK HALONG DALAM LINGKUNGAN ADAT BERBASIS KEARIFAN LOKAL - NFN Saefuddin (Multilingual, 2016)
Prohibition is one of local wisdom in traditional society. It has close relation with culture that happens inthe society. Some local people have various kind of prohibitions, it can be same or different one to another.That variation is the characteristic of each place including prohibitions that live in the society, one of themis Dayak Halong. They apply how to arrange their environment wisely base on local wisdom in the form ofprohibition. Everything that has relation with local wisdom is obeyed by all of them in the form of prohibition customary law. Base on the explanation above the problem in this study is whether prohibitions are still live in the tradition of Dayak Halong society as the form of local wisdom that happens in that society. This studyuses descriptive qualitative method. This study will get a description about various kind of prohibitions ofenvironment base on local wisdom in Dayak Halong tradition society.